Effects of the association of photobiomodulation and implantation of Biosilicate® scaffolds on the consolidation of critical-sized bone defects (Research, Society and Development, 2025)
This study aimed to evaluate the effects of photobiomodulation combined with Biosilicate® scaffold implantation on bone callus morphology 15 days after the creation of 8 mm cranial bone defects. Twenty male Wistar rats were allocated into two groups: Control Group – animals underwent bone defect induction but did not receive any treatment; and Biosilicate® + Photobiomodulation Group – animals underwent bone defect induction, received Biosilicate® scaffold implantation, and were treated with laser therapy. The laser irradiation device operated at a wavelength of 830 nm, delivering a fluence of 120 J/cm² per point. Point irradiation was applied to five different regions of the bone defect. Laser therapy was initiated immediately after surgery, with sessions performed every 48 hours, totaling seven applications. Histological analysis revealed that the combined therapy accelerated the regeneration process, as the treated group exhibited increased new bone formation, more granulation tissue, and reduced inflammatory infiltration compared with the control group. These findings suggest that combining photobiomodulation with Biosilicate® scaffolds may enhance bone healing in cases of difficult-to-treat fractures.